Ganti atau Pertahankan Tahta: Pergantian Dewan pada Eksposur dan Performa Direksi - Ihramsjah Muhamad Sadikin; Andi Manggala Putra; Anita Nopiyanti (Organum: Jurnal Saintifik Manajemen dan Akuntansi, 2022)
This study aims to board online exposure, board tenure, and firm performance to change of director in 50 non-financial indexed companies listed on the Indonesia Stock Exchange (IDX) during the 2015-2019 period. This research is quantitative research using secondary data in the form of annual reports and financial reports. This study uses Pooled Least Square (PLS) with panel regression data processed through STATA 16. The results of this study found that exposure had a positive effect on the decision to add library members. The term of office simultaneously has a negative effect on the decision to add and remove members of the board of commissioners and the library. The company's performance has a positive effect on the reduction of commissioners. Online exposure and firm performance correlate with director turnover as a corporate governance control mechanism. This research has an implication to practitioners considering that one determining factor of director turnover is their exposures.